Challenges to Teaching and Learning of Agriculture in Secondary Schools in Rubanda West Constituency Rubanda District. - Ariyo, Vincent (Kabale University, 2024)
This study aimed to investigate the challenges faced in teaching and learning agriculture in public secondary schools within Rubanda West constituency. The specific objectives were to assess the current state of agriculture education, identify institutional challenges, and examine non-institutional factors affecting agriculture teaching and learning. A descriptive survey design was employed, with data collected through questionnaires and observation checklists. The research was conducted in all secondary schools in the constituency, targeting Form Four agriculture students, headteachers, and agriculture teachers. A total of 67 respondents participated, with purposive sampling used for headteachers and agriculture teachers, and simple random sampling for students. Data were analyzed using the Statistical Package for Social Sciences (SPSS). Findings revealed that all schools offered agriculture as a subject, though it attracted fewer students compared to business studies, with which it is paired in the curriculum. Many students, however, expressed an interest in pursuing agriculture-related careers. Institutional challenges included a lack of resources such as school farms, agricultural tools, and dedicated classrooms. Other challenges involved high teacher workload and punitive practices, such as requiring students to weed flowers, which negatively impacted their attitudes toward agriculture. The study also identified non-institutional challenges such as unreliable rainfall, high poverty levels, inadequate agricultural land, and the urban backgrounds of some students. The study concluded that both institutional and non-institutional factors hinder effective agriculture teaching and learning. It recommended that schools ensure the provision of sufficient classrooms and land for practical agricultural activities. Additionally, it suggested that further research be conducted in other districts to explore the factors influencing students’ choice of agriculture as a subject, an aspect not addressed in this study.